PEDAL OPERATED MULTIPURPOSE FOOD PROCESSING UNIT - Mr. Andagi B. D; Mr. Reddi Akash N.; Mr. Kapase Abhijit R.; Mr. More Ajinkya D. (International Journal of Innovations in Engineering Research and Technology, 2021)
The present work is Design and fabrication of “PEDAL OPERATED MULTIPURPOSE FOOD PROCESSING UNIT”. This is an alternative technology to the electrically operated stationary machines with high efficiency and portability. The project is related to the food processing unit. Current activities include analysis as well as experimental work. After analysis this project has developed what quantity and what kind of raw material is required to process different food items. Under experimental work the project deals with the proper functioning of the machine. The machine is run by a person seated on a seat provided, operating the pedal which connects the machine with a chain drive to the different units of the machine, and the machine starts processing the required food items. They are potato chips, vermicelli (shevai), slices of various vegetables etc.The main purpose of the machine is not only to eliminate the usage of electricity but producing some amount of useful electricity as well. The project is portable and consumes less floor area. Thisproject is a welcome addition and a new concept where it can be thought as an ideal replacement for the electrically operated stationary machines